2004
DOI: 10.1590/s0100-879x2004000100017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to human herpesvirus-8 in populations with and without risk for infection in São Paulo State

Abstract: Human herpesvirus 8 (HHV-8) is a newly described herpesvirus that is etiologically associated with all forms of Kaposi's sarcoma (KS). Seroepidemiological studies have shown high prevalence rates of HHV-8 antibodies among men who have sex with men (MSM) and AIDS patients, African children, Brazilian Amerindians, and elderly individuals in certain regions of Europe. The aim of the present study was to determine the prevalence of HHV-8 antibodies in healthy children and young adults from different cities in São … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
(22 reference statements)
5
24
0
6
Order By: Relevance
“…HHV-8 infection is common in HIV-positive patients, being significantly higher in HIV-positive homosexual men as compared to HIV-infected patients showing other behavioral risk factors. In the present study, the prevalence of HHV-8 infection in HIV-infected mothers was not evaluated, and although in previous studies undertaken in São Paulo State, the prevalence rate of HHV-8 antibodies in women ranged from 7.9 to 18.8% (17,18), there are no data that allow us to compare these groups. The higher prevalence of HHV-8 infection in HIV-infected patients than that seen in healthy Brazilian adults, taken together with the demonstration of HHV-8 DNA in cervical scrapes from HIV-infected women (19), suggest that, theoretically, children born to HIV-infected mothers could be at risk of acquiring HHV-8 infection.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…HHV-8 infection is common in HIV-positive patients, being significantly higher in HIV-positive homosexual men as compared to HIV-infected patients showing other behavioral risk factors. In the present study, the prevalence of HHV-8 infection in HIV-infected mothers was not evaluated, and although in previous studies undertaken in São Paulo State, the prevalence rate of HHV-8 antibodies in women ranged from 7.9 to 18.8% (17,18), there are no data that allow us to compare these groups. The higher prevalence of HHV-8 infection in HIV-infected patients than that seen in healthy Brazilian adults, taken together with the demonstration of HHV-8 DNA in cervical scrapes from HIV-infected women (19), suggest that, theoretically, children born to HIV-infected mothers could be at risk of acquiring HHV-8 infection.…”
mentioning
confidence: 76%
“…IFA were performed using the BCBL-1 cell line as described previously (17). The viral lytic cycle was induced by incubating BCBL-1 cells with 20 ng/ml 12-o-tetradecanoylphorbol-13-acetate (TPA) for 96 h. Punctuate nuclear staining in untreated BCBL-1 cells was considered to indicate positivity for antibodies to LANA.…”
mentioning
confidence: 99%
“…Nineteen patients reported their ethnicity to be Caucasian, nine reported African descent, four reported mixed origin, and one patient was of Amazonian descent. Only three of the major HHV-8 subtypes were detected, with 48%, 21%, and 30% of patients harboring subtypes A, B, and C. In the same year, Souza et al 37 reported a seroprevalence study performed in 643 healthy children and young adults from the general population in ten different areas in Sao Paulo, all in high risk groups for HHV-8 infection. They found an overall seroprevalence of 2.5% among healthy children and adults from the general population using lytic IFA.…”
Section: Brazilmentioning
confidence: 99%
“…Studies regarding its presence in Brazil disclosed HHV-8 endemic populations among Amerindians and homosexual/bisexual men infected with HIV-1 [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%